Mucolytics for acute exacerbations of chronic obstructive pulmonary disease: a meta-analysis. (25th January 2023) - Papadopoulou, Efthymia; Hansel, Jan; Lazar, Zsofia; Kostikas, Konstantinos; Tryfon, Stavros; Vestbo, Jørgen; Mathioudakis, Alexander G.
This meta-analysis explored the safety and effectiveness of mucolytics as an add-on treatment for chronic obstructive pulmonary disease (COPD) exacerbations. Based on a pre-registered protocol and following Cochrane methods, we systematically searched for relevant randomised or quasi-randomised controlled trials (RCTs). We used the Risk of Bias v2 tool for appraising the studies and performed random-effect meta-analyses when appropriate. We assessed certainty of evidence using GRADE. This meta-analysis included 24 RCTs involving 2192 patients with COPD exacerbations, entailing at least some concerns of methodological bias. We demonstrated with moderate certainty that mucolytics increase the rate of treatment success (relative risk 1.37, 95% CI 1.08–1.73, n=383), while they also exert benefits on overall symptom scores (standardised mean difference 0.86, 95% CI 0.63–1.09, n=316), presence of cough at follow-up (relative risk 1.93, 95% CI 1.15–3.23) and ease of expectoration (relative risk 2.94, 95% CI 1.68–5.12). Furthermore, low or very low certainty evidence suggests mucolytics may also reduce future risk of exacerbations and improve health-related quality of life, but do not impact on breathlessness, length of hospital stay, indication for higher level of care or serious adverse events. Overall, mucolytics could be considered for COPD exacerbation management. These findings should be validated in further, rigorous RCTs. A meta-analysis of 24 RCTs (N=2192) demonstrated with moderate certainty that mucolytics can improve treatment success rate by 37% and significantly improve symptoms in COPD exacerbations #AECOPD. There were no safety signals. https://bit.ly/3RwTzlU